2008
DOI: 10.5194/angeo-26-201-2008
|View full text |Cite
|
Sign up to set email alerts
|

Multi-instrumentation observations of a transpolar arc in the northern hemisphere

Abstract: Abstract.A transpolar arc was imaged by the FUV instrument on the IMAGE spacecraft during a 3-h interval on 5 February 2002. Observations indicate that a burst of reconnection in the geomagnetic tail, which was not associated with a substorm, was responsible for the formation of the arc. The arc initially formed across the central polar cap, extending from near midnight to noon such that the polar cap was approximately divided in half. The subsequent motion of the arc was controlled by the amount of open flux … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
34
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 31 publications
5
34
0
Order By: Relevance
“…We focus on two clear dawn‐dusk motions of PCAs, at 20:23 and 23:08 UT (highlighted by the two vertical red lines) after the IMF B y polarity changes with a 69 min time delay to allow the IMF variations propagating through the magnetosphere. This clearly shows that IMF B y polarity change or strong magnitude change can trigger the existing PCA to move poleward, which confirms many previous studies (Fear & Milan, ; Goudarzi et al, ; Kullen et al, ; Milan et al, ). One point to note regarding the optical observation is that the intensity of 557.7 nm is much higher than the 630.0 nm intensity.…”
Section: Observationssupporting
confidence: 90%
See 1 more Smart Citation
“…We focus on two clear dawn‐dusk motions of PCAs, at 20:23 and 23:08 UT (highlighted by the two vertical red lines) after the IMF B y polarity changes with a 69 min time delay to allow the IMF variations propagating through the magnetosphere. This clearly shows that IMF B y polarity change or strong magnitude change can trigger the existing PCA to move poleward, which confirms many previous studies (Fear & Milan, ; Goudarzi et al, ; Kullen et al, ; Milan et al, ). One point to note regarding the optical observation is that the intensity of 557.7 nm is much higher than the 630.0 nm intensity.…”
Section: Observationssupporting
confidence: 90%
“…In addition, Kullen et al () confirmed the previously reported statistical relationship between PCAs and reconnection‐induced flows in the ionosphere, implicitly indicating that an IMF B y sign change does not trigger the formation of a PCA, though it does cause a dawn‐dusk motion of an already existing PCA over the polar cap. Many other previous studies have also showed that the IMF B y polarity change (or strong magnitude change) can trigger the existing PCA to move over the polar cap (Fear & Milan, ; Goudarzi et al, ; Milan et al, ). When the IMF B y sign is positive (negative), a PCA can separate from the dusk (dawn) oval side and move across the polar cap in the Northern Hemisphere (Frank et al, ; Huang et al, ; Kullen et al, ; Milan et al, ) and the IMF B y has an opposite effect on the motion of PCAs in the Southern Hemisphere (Craven et al, ).…”
Section: Introductionmentioning
confidence: 89%
“…As more and more flux is closed in this magnetic local time (MLT) sector, the trapped field lines will protrude deeper into the magnetotail lobes. This mechanism has been validated by several different case studies [e.g., Goudarzi et al , ; Fear et al , ]. Furthermore, the main predictions from the mechanism, i.e., a delay in the MLT dependence on the IMF B y and an association with TRINNI flows, have been statistically verified by Fear and Milan [, ].…”
Section: Introductionmentioning
confidence: 63%
“…Predictions from this mechanism have been verified by Fear and Milan (), who explored the relation between the position where arcs formed in the polar cap and the IMF B y component, and Fear and Milan (), who found statistical evidence for reconnection‐induced flows in the ionosphere before the formation of the TPAs. Furthermore, several recent case studies have also provided evidence in support of this mechanism (e.g., Carter et al, ; Fear et al, ; Goudarzi et al, ).…”
Section: Introductionmentioning
confidence: 92%